Accumulation Of Heavy Metals in Bee Products Effect of Distance From Highway - Servet Arslan; Adem Arıkan (Turkish Journal of Agriculture: Food Science and Technology)
Distance from the highway to the effect of heavy metal accumulation in bee products in order to investigate in this study; four different apiaries which have four km interval have been established from Tokat-Turhal highway side towards the north. Each station of a total 9 of 36 units bee colonies were placed. Honey, pollen and propolis samples were taken from these colonies in the months of April-July in 2009. The obtained samples (copper, zinc, iron, cadmium, chromium, lead and heavy metals such as manganese) content were investigated. According to the distance from the highway in honey samples averages of zinc, iron, chromium and manganese, there was no statistical difference between averages, while averages of copper, cadmium and lead were found significant differences between the averages. In the pollen samples, averages of zinc, iron, cadmium, chromium and manganese indicated no statistical difference between the averages, while, averages of copper and lead were found to be statistically significant. İn the Propolis samples, averages of copper, zinc, iron, chromium, lead and manganese determined no statistical difference between the averages, significant differences were detected between the averages of cadmium. Cadmium accumulation in the maximum occurs at the edge of the highway, the maximum accumulation of other metals have been seen in other stations When considering, due to traffic only metal cadmium at a level that considered as important in bee products be said to constitute pollution.